Socioeconomic determinants of health. The contribution of nutrition to inequalities in health. - James, W. P. (1997)
Social class differences in health are seen at all ages, with lower socioeconomic groups having greater incidence of premature and low birthweight babies, heart disease, stroke, and some cancers in adults. Risk factors including lack of breast feeding, smoking, physical inactivity, obesity, hypertension, and poor diet are clustered in the lower socioeconomic groups. The diet of the lower socioeconomic groups provides cheap energy from foods such as meat products, full cream milk, fats, sugars, preserves, potatoes, and cereals but has little intake of vegetables, fruit, and wholewheat bread. This type of diet is lower in essential nutrients such as calcium, iron, magnesium, folate, and vitamin C than that of the higher socioeconomic groups. New nutritional knowledge on the protective role of antioxidants and other dietary factors suggests that there is scope for enormous health gain if a diet rich in vegetables, fruit, unrefined cereal, fish, and small quantities of quality vegetable oils could be more accessible to poor people.